The Effectiveness of Learning Song Media on Learning Outcomes in the Science Food Chain - Lisa Haqiqul Zana; Afrijal Afrijal (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
Low science learning outcomes in elementary schools are often caused by conventional methods that are less interesting, so students are passive and have difficulty understanding abstract concepts. This study aims to measure the effectiveness of song media in improving science learning outcomes for fifth-grade students at SDN 1 Panca Jaya. This study employed a quantitative, quasi-experimental design with a sample of 38 students divided into two groups: an experimental group that used songs and a conventional control group. This study collected data through observation, tests, and documentation. The test was conducted twice: a pre-test and a post-test. Data analysis was conducted by calculating the N-Gain to assess improvements in student learning outcomes. The results showed that the average post-test and N-Gain of the experimental group were higher than the N-Gain of the control group, namely 0.85. This indicates that song media is effective in creating a fun learning atmosphere and facilitating understanding of the material. It was concluded that song media can be an effective learning strategy to improve student learning outcomes in science.